Casos reais de implantaç\~ao do modelo de gest\~ao do conhecimento para administraç\~ao pública Brasileira: O caso da fundaç\~ao Oswaldo Cruz - Fábio Ferreira Batista; Paula Xavier dos Santos; Ana Cristina da Matta Furniel; Ana Paula Carvalho; Carla Xavier dos Santos Kaufmann; Erica de Castro Loureiro; Rodrigo Ferrari (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper analyzes how three departments of Oswaldo Cruz Foundation - Fiocruz implemented the Knowledge Management Framework for the Brazilian Public Administration as well as the KM implementation method presented in a book published by the Institute of Applied Economic Research - Ipea (Batista, 2012). Each one of the departments (Oswaldo Cruz House, Human Resources Department and Bio-Manguinhos) implemented three of the four steps of the method: step 1: Assessment; step 2: Planning and step 3: Development. The main outcomes of the KM initiative so far are: KM alignment with the strategic goals of the organization; KM plans designed by the departments; Batista's method adaptation to Fiocruz and review; beginning of the KM practices implementation; institutionalization of KM multidisciplinary teams to provide support for the implementation of KM processes; creation of a positive environment to accept KM as management method; leadership and strategic stakeholders' participation in the implementation of the KM initiative; and the establishment of the foundation for the establishment of a KM policy in the organization. The second phase of the KM initiative is scheduled to be implemented in 2015 and it is made of two activities: KM practices implementation in the three departments (Oswaldo Cruz House, Human Resources Department and Bio-Manguinhos) and the adoption of the KM implementation method by other Fiocruz departments.
Keywords: H80; 330; knowledge management; public administration; public health organizations